Penerapan Tipografi dalam Sistem Signage pada Interior Ruang Publik - Ruki, Ulli Aulia; Nediari, Amarena (Bina Nusantara University, 2014)
Signage system is applied in interior public spaces with consideration to the basic of typography. The objective of signage system is to provide the user convenience in public spaces in order to reach destination while the user is in the building. The basic requirements for designing signage system are legibility and readability. There are still designers who are not aware about the importance of designing a signage system so that sometimes it is found only as decorative element. It is necessary to make the best use of the purpose of signage design, so an interior design should be more carefully in conducting research related to the application of signage system in public spaces. The applied typography has to be considered by its size, placement, colors, and materials to be used. This research used design thinking goal grid method that is suitable to examine the signage system in order to complete design objectives. Article focuses on how to design the signage system to accommodate information that was useful for the user in public space. At the end, there would be identified signage system’s function in interior public spaces as information, guidance, identification as well as safety regulation.